Running speed increases plantar load more than per cent body weight on an AlterG® treadmill - Thomson, A.; Einarsson, E.; Witvrouw, E.; Whiteley, R. (Journal of Sports Sciences, 2017)
AlterG® treadmills allow for running at different speeds as well as at reduced bodyweight (BW), and are used during rehabilitation to reduce the impact load. The aim of this study was to quantify plantar loads borne by the athlete during rehabilitation. Twenty trained male participants ran on the AlterG® treadmill in 36 conditions: all combinations of indicated BW (50-100%) paired with different walking and running speeds (range 6-16 km · hr-1) in a random order. In-shoe maximum plantar force (Fmax) was recorded using the Pedar-X system. Fmax was lowest at the 6 km · hr-1 at 50% indicated BW condition at 1.02 ± 0.21BW and peaked at 2.31 ± 0.22BW for the 16 km · hr-1 at 100% BW condition. Greater increases in Fmax were seen when increasing running speed while holding per cent BW constant than the reverse (0.74BW-0.91BW increase compared to 0.19-0.31BW). A table is presented with each of the 36 combinations of BW and running speed to allow a more objective progression of plantar loading during rehabilitation. Increasing running speed rather than increasing indicated per cent BW was shown to have the strongest effect on the magnitude of Fmax across the ranges of speeds and indicated per cent BWs examined.